Acceptability and feasibility study of a six-week person-centred, therapeutic visual art intervention for people with dementia. Issue 3 (2nd September 2021) - Shoesmith, Emily; Charura, Divine; Surr, Claire
ABSTRACT: Background: There has been increasing interest in dementia, the arts and creativity across different disciplines in recent years, with previous literature illustrating the benefits of visual arts for people with dementia. Method: A mixed-methods, quasi-experimental, pre/post design to assess the feasibility, acceptability and preliminary efficacy of a newly developed therapeutic, person-centred visual art intervention for people with dementia attending a day care centre or residing in an assisted living facility. Results: Five themes were identified from the interviews. Two themes reflected the feasibility/acceptability and the perceived impacts of the intervention, and three themes represented perceived successful elements: participant choice, socialisation and mentally stimulating activities. The quantitative data tentatively indicated enhanced social functioning and quality of life scores post-intervention. Conclusion: These findings indicate that engagement with visual art is effective for people with dementia, and taking into account the factors that impact on feasibility and acceptability will promote future robust evaluation.